Studi Quran Kontemporer : Telaah Atas Hermeneuitik Quran Nashr Hamid Abu Zayd - Alfitri Alfitri (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2002)
The contemporary qur'anic studies have been marked by amazing development. Various methods and approaches to understand the Qur'an are offered by the scholars. One of prominent figures in this field is Nashr Hamid Abu Zayd. He is an Egyptian scholar whom accused of being apostate, because of his theory of qur'anic hermeneutic (the textual of Qur'an). This article aims at discuss why Abu Zayd's theory has been string up Islamic world and ending by his expulsive from his native country. To deal with this problem, in this article discusses Abu Zayd's biography and some cultural framework of his people. The methodology of qur'anic hermeneutic is the least his theoritical fromont in qur'anic interpretation. Having examined the topic, the author finds this Abu Zayd believes that modem literary theory and criticism denote the way to understandand interpret the Qur'an